PERAN DATA KOMPOSISI POPULASI TERNAK SAPI POTONG DALAM PERENCANAAN PENCAPAIAN KECUKUPAN DAGING SAPI DI PROVINSI PAPUA BARAT - Trisiwi Wahyu Widayati; Sri Widodo; Masyhuri Masyhuri; Any Suryantini (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2009)
The purpose of this study is to demonstrate the important role of livestock population data with the detail the composition according to age and gender in planning the provision of meat in the province of Papua in particular to correlate the number of mother cows and cattle are ready to cut the amount of output produced in a given year. Problem-solving method using descriptive analytical approach to the tabulation and analysis tools OLS. The sample of 189 respondents used. Sample areas in Manokwari. The results showed that the relationship of parent and output data beef cattle that could be used for planning the achievement of the adequacy of the best of the best beef in West Papua obtained from the parent relations cow - calf male (age <1 year) with a number R2 0.822, with a coefficient of relationship 0.442. To produce a ready cattle bulls (age> 2 years) in the year amounted to 2.26 t required parent tail invested two years earlier.Keywords: Population Composition Data, Mother Cow, calf (Output)